Kazakhstan As A Model For The Study Of Political Culture In A Poly-Cultural Society - Ilimkhanova, L.; Adilova, K.; Nurtazina, R.; Kalaganov, B.; Baimoldina, S.; Bugybay, D. (Opción, 2019)
Every nation, to one extent or another, has the right to its own opinion and promotion of its own vision of political ideals and value contents. In this context, there should not go without mention the other countries’ negative experience on their way towards modernization and transition from the industrial to post-industrial structure. Accent should be put on the fact that even the best world examples disregarding the state national characteristics will not be accepted by the society, resulting in hostile attitude growth. Such changes are dangerous enough for Russia as a multinational state.Wrong interpretation of the methods to improve the population quality of life might lead to interethnic or inter-religious hostility, discrediting the democracy concept itself and inciting regress in the country development process. According to many researchers’ opinion, the contemporary government is one of the most important research institutes of political culture determinants. Government appears as a result of the nation long-lasting historical development, its changes representing effective factors hindering or accelerating certain individual political culture patterns emergence. . Nevertheless, a detailed overview of the respective issue requires studying the entry of the “political culture” concept, the interaction of this phenomenon determinants, and becoming aware of the significance of government as an institute of research on the political culture elements and transformations in terms of the society impact and attitude.